Stem cell therapy in the heart: Biomaterials as a key route. (August 2021) - Hashemzadeh, Mohammad Reza; Taghavizadeh Yazdi, Mohammad Ehsan; Amiri, Mohammad Sadegh; Mousavi, Seyed Hadi
Highlights: Stem cell therapy, as a novel therapeutic way, shows great promise in the treatment of heart diseases in recent years. Stem cell delivery methods into the heart are a big challenge that can be modified by biomaterial utilization. The incorporation of stem cells into natural scaffolds has promoted a bloom of development in regenerative therapy. Natural biomaterials can regulate the proliferation and differentiation of implanted stem cells into the target tissue. The majority of natural biomaterials are injectable and mechanically stable enough to tolerate the beating of the heart. Abstract: Cardiovascular diseases are one of the main concerns, nowadays causing a high rate of mortality in the world. The majority of conventional treatment protects the heart from failure progression. As a novel therapeutic way, Regenerative medicine in the heart includes cellular and noncellular approaches. Despite the irrefutable privileges of noncellular aspects such as administration of exosomes, utilizing of miRNAs, and growth factors, they cannot reverse necrotic or ischemic myocardium, hence recruiting of stem cells to help regenerative therapy in the heart seems indispensable. Stem cell lineages are varied and divided into two main groups namely pluripotent and adult stem cells. Not only has each of which own regenerative capacity, benefits, and drawbacks, but their turnover also close correlates with the target organ and/or tissue as well as the stage and level of failure. In addition to inefficient tissue integration due to the defects in delivering methods and poor retention of transplanted cells, the complexity of the heart and its movement also make more rigorous the repair process. Hence, utilizing biomaterials can make a key route to tackle such obstacles. In this review, we evaluate some natural products which can help stem cells in regenerative medicine of the cardiovascular system.